Peningkatan Pembelajaran Senam Keseimbangan Melalui Pendekatan Bermain Meniru Gerak Binatang di Lingkungan Persawahan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
This research is a classroom action research with two cycles of execution. Subjects in this study were students of class III of MI Islamiyah Karangdawa Margasari Tegal Regency, amounting to 36 studentsData collectiontechniques using observational methods, performance, and documentation questionnaire with three aspects:cognitive, affective and psychomotor.The percentage of first cycle thoroughness only 75% to 92% meansmastery of learning outcomes of students has increased by 17%, while the success of the second cycle was 92%and students who have not completed 8%. The results showed that the learning outcomes gymnastics balancethrough playing approach imitating the movement of animals in the rice fields in class III of MI IslamiyahKarangdawa Margasari Tegal Regency show a positive impact